Arbuscular Mycorrhizal Fungi and Glomalin - Aydın Atakan; Hülya Özgönen Özkaya (Turkish Journal of Agriculture: Food Science and Technology)
The interactions between plant, soil, and mycorrhizal fungi are ecologically and agriculturally beneficial systems. Mycorrhizal fungi are capable of forming a symbiosis with the roots of many plants in nature. In this symbiosis, the plant receives help from the mycorrhizal fungus in nutrient and water uptake. On the other hand, the mycorrhizal fungi supply the assimilant products they need from the plant. In addition to the many benefits of AMF, they have very important roles in carbon (C) storage in the soil. These roles of AMF are associated with the production of a substance named “Glomalin”. Glomalin, an N-linked glycoprotein that is considered to be AMF gene products, is defined as a protein secreted by AMF hyphae and spores. Glomalin significantly reduces the degradation of soil organic matter by preserving unstable compounds in soil aggregates. Glomalin, which helps soil aggregation, is also an excellent hyphae protector.